The equipment for directly cleaning of the combustion engine eject needle - Nguyễn Huỳnh Minh; Nguyễn Hữu Trường (Journal of Technical Education Science, 2014)
The paper presents the results of the research, the design, and the new manufacture that is the directly cleaning eject needle equipment of the combustion engine which is used in electronic fuel-injected engine. It combines with the cleaning proposed fuel and let shorten the maintain engine time (no need take eject needle away the engine). The equipment operates safely and exactly, it has high economic effects. It is new equipment made in Vietnam and it combines with great progress of electronic and information technology that contributes to reduce the environmental pollution. The equipment is applied for the fuel and diesel injection-engine, that they are installed in the automobile at EURO 2 standard (European emission standards). The result of the research could applies in manufacture reality with low cost, in accordance with domestic ability technology, and shorten the maintain time for the fuel-injected combustion engine.